Monowave and polywave light-curing of bulk-fill resin composites: degree of conversion and marginal adaptation following thermomechanical aging - Contreras, Sheila Celia Mondragón [UNESP] (2021)
Aim: This study aimed to evaluate the effect of polymerization with either a monowave (MW) or a polywave (PW) light-curing unit (LCU) on the degree of conversion (DC) and marginal adaptation following thermomechanical aging of an ormocer bulk-fill resin composite (RC) (Admira fusion X-tra Bulk Fill–AB), a methacrylate-based bulk-fill RC (Tetric N-Ceram Bulk Fill–TB) and a conventional RC (Tetric N-Ceram–TC). Methods: DC was assessed in five samples of each RC using Fourier transform infrared spectroscopy. For determination of marginal adaptation, standard preparations were made in 60 bovine incisors, divided into three groups, according to the RC. The bulk-fill RC was inserted in a single increment of 4 mm. In contrast, the conventional RC was inserted in three increments. Marginal gap was evaluated after thermomechanical aging. Data were analyzed using a two-way analysis of variance (ANOVA) and Tukey’s tests for multiple comparisons (α = 0.05). Results: The two-way ANOVA showed a significant effect (p<.05) of the RC factor but not of the LCU factor. The Tukey test showed that TB had the significantly lowest DC followed by TC, and with AB having the significantly highest DC. For the marginal adaptation, a significant effect was found for the LCU factor and the for the interaction RC × LCU (p<.05). Groups light-cured with PW showed significantly wider marginal gaps than MW. TC presented wider marginal gaps (17.36 µm) when cured with PW than when cured with MW (13.05 µm). The two bulk-fill RC resulted in similar marginal gap formation to each other. Conclusion: The ormocer-based bulk-fill RC showed a higher DC than the methacrylate-based bulk-fill RC but similar marginal adaptation. The LCU, MW or PW, had no significant influence on the DC, and no relevance on the marginal adaptation.